Review Article : Pharmacology GS-441524, Source, Pharmacodynamics, Pharmacokinetics, And Efficacy in Treatment of Feline Infectious Peritonitis - ismi nurjannah (Hasanuddin University, 2026)
Feline infectious peritonitis (FIP) is a historically fatal disease caused by a virulent mutation of feline coronavirus, characterized by systemic inflammation, immune dysregulation, and high mortality in untreated cats. The emergence of GS-441524, an adenosine nucleoside analog targeting viral RNA-dependent RNA polymerase (RdRp), has transformed the therapeutic outlook for FIP and represents a significant shift from palliative management to effective antiviral intervention. This review aims to synthesize current evidence on the pharmacology, therapeutic efficacy, safety, accessibility, and regulatory considerations surrounding GS-441524, while identifying remaining knowledge gaps and priorities for future research. GS-441524 demonstrates favorable pharmacokinetic and pharmacodynamic properties, including efficient cellular activation, strong antiviral potency, and adequate tissue distribution, with high clinical success rates across effusive, non-effusive, ocular, and neurological forms of FIP. Its safety profile is generally acceptable, though injection-site reactions, limited penetration into protected compartments, and variability in unregulated formulations present ongoing challenges. Regulatory inaccessibility remains a major barrier in many countries, driving reliance on black-market products and underscoring the need for evidence-based veterinary approval pathways. Overall, GS-441524 represents a highly effective antiviral agent with substantial potential to redefine FIP treatment standards. Continued research is needed to clarify resistance mechanisms, optimize dosing strategies, improve pharmaceutical standardization, and advance regulatory acceptance to ensure safe, reliable, and equitable access for feline patients.